Penerapan Model Pembelajaran Kooperatif Jigsaw untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Pelajaran Produk Kreatif Kewirausahaan: SMK Semen Padang (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research is a Classroom Action Research (CAR) conducted in two cycles. The subjects were 24 students of class XII TM 2 of the Mechanical Engineering Expertise Program at Semen Padang Vocational School in the odd semester of the 2025/2026 academic year. Data collection was carried out through learning activity observation sheets, practical assessment sheets, and multiple-choice tests to measure students' cognitive learning outcomes. The implementation of Creative Products and Entrepreneurship learning at Semen Padang Vocational School was previously teacher-centered. Students tended to be passive listeners during the learning process, which led to low participation, minimal interaction, and a lack of understanding of the material. As a result, most students were unable to achieve the Minimum Completion Standards (SKM). Based on this, the Jigsaw Cooperative learning model is considered suitable for application in Creative Products and Entrepreneurship learning, because it is able to create a student-centered learning atmosphere and encourage active involvement and cooperation between students. The results of the study prove that the application of the Jigsaw Cooperative learning model is effective in improving student learning outcomes. This is based on the average student learning outcomes in cycle 1 of 75.2, where 17 students were declared complete. In cycle II, the average student learning outcomes were 85.2 with 21 students declared complete. The significant improvement in cycle II indicates that the Jigsaw Cooperative Learning model is not only effective in improving cognitive learning outcomes but also able to improve the quality of interactions between students in the learning process. Students become more active in discussions, disseminating information, and are responsible for understanding the material they are learning and sharing with their groups.